TOXICOLOGICAL ASSESSMENT OF FOOD ADDITIVE: "YODAZIN" - Shaykhova Guli Islamovna; Muratov Sarvar Akbarganovich; Zokirkhonova Shahzoda Asatovna; Ashurova Mukaddas Djaloldinovna; Rakhimova Durdona Zhurakulovna; Utamurodova Nigora Abdurakhmanovna (The Bioscan, 2025)
The increasing use of food additives in the food industry necessitates rigorous toxicological evaluation to ensure consumer safety. This study aimed to assess the potential toxicity of Yodazin, a commonly used food additive, through a series of in vitro and in vivo experiments. Acute and sub-chronic toxicity studies were conducted using rodent models to evaluate the effects of Yodazin on physiological, biochemical, and histopathological parameters. Additionally, genotoxicity assays, including the Ames test and micronucleus assay, were performed to determine its mutagenic potential. The results indicated that Yodazin exhibited low acute toxicity, with an LD₅₀ value exceeding 5000 mg/kg body weight. However, sub-chronic exposure at high doses led to mild hepatic and renal alterations, suggesting a need for dose regulation. No significant genotoxic effects were observed in the tested models. These findings suggest that while Yodazin is relatively safe at recommended levels, prolonged excessive consumption may pose health risks. Further long-term studies are recommended to establish its safety profile comprehensively.